An unusual case of chylothorax complicating childhood tuberculosis - KARADAĞ, BÜLENT TANER; KIYAN, GÜRSU (WILEY, 2008)
Endobronchial tuberculosis (EBTB) and chylothorax are rare clinical disorders. The concurrence of these two disorders as manifestations of childhood pulmonary tuberculosis has not been reported. We report a 4-month-old boy presenting with chylothorax as the initial presentation of tuberculosis that has been successfully treated with octreotide, antituberculosis drugs and steroid therapy.
Keywords: chylothorax; endobronchial tuberculosis; child; ENDOBRONCHIAL TUBERCULOSIS; PULMONARY TUBERCULOSIS; BRONCHOSCOPY; MANAGEMENT; CHILDREN; SOMATOSTATIN; OCTREOTIDE; LYMPHOMA